2020
DOI: 10.1007/s11102-020-01038-y
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the Acromegaly Treatment Satisfaction Questionnaire (Acro-TSQ) in adult patients with acromegaly, including correlations with other patient-reported outcome measures: data from two large multicenter international studies

Abstract: Purpose The Acromegaly Treatment Satisfaction Questionnaire (Acro-TSQ) is a new patient-reported outcome (PRO) measure for patients with acromegaly receiving injectable somatostatin analogs (SSAs) to assess clinical symptoms and adverse drug reaction interference, treatment satisfaction, and convenience. We evaluated its scale structure, reliability, validity, responsiveness, and what constitutes clinically meaningful change. Methods Data from two longitudinal studies (N = 79 and 82) of patients receiving a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 25 publications
0
28
0
3
Order By: Relevance
“…Results of the longitudinal surveillance ACROSTUDY similarly showed improvement in QOL with pegvisomant using both AcroQoL and PASQ questionnaires [ 33 ]. A patient-centric approach for QOL assessment may allow a more personalized method of management [ 34 ], and tools such as the recently developed Acromegaly Treatment Satisfaction Questionnaire (Acro-TSQ) also show improved QOL with disease control [ 11 ], specifically in patients treated with injectable SRL [ 35 ]. However, addressing the high discordance between patient- and medical provider-reported symptom severity, pattern of acromegaly symptoms, and treatment injection site reactions remains a challenge for treating physicians [ 12 ].…”
Section: Presentation Comorbidities and Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Results of the longitudinal surveillance ACROSTUDY similarly showed improvement in QOL with pegvisomant using both AcroQoL and PASQ questionnaires [ 33 ]. A patient-centric approach for QOL assessment may allow a more personalized method of management [ 34 ], and tools such as the recently developed Acromegaly Treatment Satisfaction Questionnaire (Acro-TSQ) also show improved QOL with disease control [ 11 ], specifically in patients treated with injectable SRL [ 35 ]. However, addressing the high discordance between patient- and medical provider-reported symptom severity, pattern of acromegaly symptoms, and treatment injection site reactions remains a challenge for treating physicians [ 12 ].…”
Section: Presentation Comorbidities and Mortalitymentioning
confidence: 99%
“…(HQ, SR) Rationale: In clinical trials, OOC was initiated at the time of the next SRL injection, i.e., at the end of the once-monthly injection period [ 4 , 9 ]. IGF-I levels may increase toward the end of the injection period with waning of injectable drug levels [ 10 ], and likely account for reported exacerbation of acromegaly symptoms [ 11 13 ] How should OOC dose be escalated? OOC can be up-titrated by an increment of 20 mg every 2–4 weeks based on IGF-I and clinical symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Sample items from the survey are included in a supplemental file. The online survey also included the Acro-TSQ, an acromegaly-specific PRO assessing symptom and GI side effect interference, treatment satisfaction, treatment bother, and treatment convenience [16,17]. The Acro-TSQ contains 24 items and was developed in line with recommendations by the Food and Drug Administration in a published document containing guidelines for PRO development which included qualitative research with individuals with acromegaly [12].…”
Section: Study Type and Patient Populationmentioning
confidence: 99%
“…However, these agents require deep tissue injection and can be associated with substantial treatment burden or deleterious long-term sequelae, including injection site pain, nodules, bruising, inflammation, and scarring ( 2 , 10 ). Injectable SRLs may also negatively affect patient quality of life; patients have reported anxiety, frustration, and loss of independence caused by the injections ( 10 , 11 ). Although some patients are able to safely and effectively receive injections at home, a recent study found that only 17% of patients with acromegaly are receiving injections in this manner ( 10 , 12 , 13 ).…”
mentioning
confidence: 99%